Pathways to Karlsruhe: A Sequence Analysis of the Careers of German Federal Constitutional Court Judges. Issue 1 (2nd January 2016) - Jäckle, Sebastian
Abstract : Judges of the German Federal Constitutional Court can be seen as both judicial and political elites. Yet up to now there is no systematic work on the Court's' judges and especially their careers prior to their appointments. Using sequence analysis, this article identifies four relatively distinct clusters of career characteristics: academia, administration (and administrative courts), ordinary jurisdiction and politics. Judges whose career background is limited to the judicial sphere mostly advance from a level below the Länder to the Länder and then on to the federal level, while those with a background in politics or administration switch less often among them. Furthermore, little evidence was found to suggest that differences in the judges' career paths can be explained by reference to the body that elected them (Bundestag or Bundesrat) or the party that nominated them (CDU/CSU or SPD). The article also illustrates the possibilities of sequence analysis for elite studies.